KEKUASAAN MENURUT TAQIYUDDIN AN-NABHANI DALAM TINJAUAN ETIKA POLITIK - Mohamad Topan (Jurnal Filsafat "WISDOM", 2013)
This study aims to explain legitimacy of power which is the basic of Taqiyuddin An-Nabhani conception of power from the perspective of political ethics theory, and to understand its relevance to the political movement of Hizbut-Tahrir in Indonesia. The results of this study are: first, the power in the basic concept of political ethics orients to benevolence and social welfare; second, the An-Nabhani concept of power is closely related to dakwah (propagation) of Islam; third, the ethical dimension of his concept of power has an objective to continue Islamic life and spread Islam throughout the world by dakwah; fourth, Hizbut-Tahrir, as a manifestation of Islamic political movement which proclaim re-establishment of Daulah Khilafah Islamiyah and implementation of syariah, in practice, will face the diversity and plurality of Indonesia.